Desenvolvimento de sistema automatizado de avaliação tridimensional para análise radiométrica em feixes de radioterapia - Fernandes, Marco Antonio Rodrigues [UNESP]; Café, Ana Flavia de Castro Kohlrauch; Andrade, Pedro Henrique Quideroli de; Silva, William Gregório Rodrigues da (My University, 2012)
This work presents the methodology developed for modelling of a threedimensional table of evaluation (X-Y-Z axes) for analysis of the radial and axial profile of radiation beams during dosimetry procedures. Available resources of free softwares and the Inventor Professional were used for dimensioning and simulation of the pieces that constitute the automated system of measurement. The modelling of the table was based on similar instruments of use in the routine of the Radiotherapy Services. It is intended to illustrate the importance of the domain of the mecatronic engineering concepts and to motivate the students’ participation in projects of researches that assist the needs of several segments of activities. The results reinforce the benefits obtained in the application executes of the interrelation of disciplines proposed in the Pedagogic Project of the Course.

Este trabalho apresenta a metodologia desenvolvida para modelamento de uma mesa de avaliação tridimensional (eixos X-Y-Z) para análise do perfil radial e axial de feixes de radiação durante procedimentos de dosimetria. Foram utilizados recursos disponíveis de softwares livres e o Inventor Professional para dimensionamento e simulação das peças que constituem o sistema automatizado de medição. A modelagem da mesa foi baseada em instrumentos similares de uso na rotina dos Serviços de Radioterapia. Pretende-se ilustrar a importância do domínio dos conceitos da engenharia de mecatrônica e incentivar a participação dos estudantes em projetos de pesquisas que atendam as necessidades de diversos segmentos de atividades. Os resultados reforçam os benefícios obtidos na aplicação efetiva da interdisciplinaridade proposta no Projeto Pedagógico do Curso.
Development of automated system of three-dimensional evaluation for radiometric analysis in radiotherapy beams
Keywords: Engineering; Design; Table XYZ; CAD software; Threedimensional movement; Engineer; Table X-Y-Z; Software of CAD; Threedimensional movement; Radiation